Evaluation of electronic translation tools through quality parameters - Kučiš, Vlasta (Array, 2009)
In the paper, the difference of translation quality of texts obtained through traditional reference works and online electronic translation tools (corpus and multilingual terminology database) will be measured in three main categories: lexical, orthographic and punctuation ; syntactically and stylistically using paired samples t-test. The translation was made with the support of electronic translation tools, using the example of a Slovenian bilingual corpus called Evrokorpus and the multilingual terminology database Evroterm. In the paper, the hypothesis that modern online translation tools contribute to the quality and consistency of expert translations, as well as to the acquisition of new competitive skills and knowledge is to be examined.